2019
DOI: 10.1158/2326-6066.cir-19-0036
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting LILRB4/APOE Interaction by an Efficacious Humanized Antibody Reverses T-cell Suppression and Blocks AML Development

Abstract: Therapeutic strategies are urgently needed for patients with acute myeloid leukemia (AML). Leukocyte immunoglobulinlike receptor B4 (LILRB4), which suppresses T-cell activation and supports tissue infiltration of AML cells, represents an attractive drug target for anti-AML therapeutics. Here, we report the identification and development of an LILRB4specific humanized mAb that blocks LILRB4 activation. This mAb, h128-3, showed potent activity in blocking the development of monocytic AML in various models includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 39 publications
(52 reference statements)
2
62
0
Order By: Relevance
“…The same cluster exhibits high expression of IL4I1, NFKBIA, VISTA , and LILRB4 . Like LILRB2, LILRB4-mediated ITIM signaling has a strong effect on the anti-inflammatory phenotype of myeloid cells ( 133 ), and we hypothesize that LILRB4 could act as a central regulator of the immunosuppressive cascade network in this myeloid cluster, as Deng et al ( 134 ) showed a significant decrease of NFKBIA (IκB) at the protein level, following genetic ablation of LILRB4 in myeloid cells ( 135 ). The additional correlation to VISTA within the same cluster is of particular importance, as VISTA is proving to be an attractive target to prevent inhibition of T-cell cytotoxicity ( 136 ).…”
Section: Tam/mdsc Identification Across Tumor Typesmentioning
confidence: 88%
“…The same cluster exhibits high expression of IL4I1, NFKBIA, VISTA , and LILRB4 . Like LILRB2, LILRB4-mediated ITIM signaling has a strong effect on the anti-inflammatory phenotype of myeloid cells ( 133 ), and we hypothesize that LILRB4 could act as a central regulator of the immunosuppressive cascade network in this myeloid cluster, as Deng et al ( 134 ) showed a significant decrease of NFKBIA (IκB) at the protein level, following genetic ablation of LILRB4 in myeloid cells ( 135 ). The additional correlation to VISTA within the same cluster is of particular importance, as VISTA is proving to be an attractive target to prevent inhibition of T-cell cytotoxicity ( 136 ).…”
Section: Tam/mdsc Identification Across Tumor Typesmentioning
confidence: 88%
“…Antibody variable region genes were cloned from those positive B cells using methods described previously. 20 Expression and purification of mAbs Full length IgG was produced in human embryonic kidney Expi293F cells using an ExpiFectamine 293 Transfection Kit (Catalog #: A14528, Gibco) by cotransfection HEK293 cells with both heavy and light chain expression constructs. 20 After 7 days of fed-batch culture, the culture supernatants were harvested and antibodies were purified by affinity chromatography using protein A resin (Catalog #: 10-2001-XM, Repligen) as described previously.…”
Section: Generation Of Anti-lilrb1 Mabsmentioning
confidence: 99%
“…20 Expression and purification of mAbs Full length IgG was produced in human embryonic kidney Expi293F cells using an ExpiFectamine 293 Transfection Kit (Catalog #: A14528, Gibco) by cotransfection HEK293 cells with both heavy and light chain expression constructs. 20 After 7 days of fed-batch culture, the culture supernatants were harvested and antibodies were purified by affinity chromatography using protein A resin (Catalog #: 10-2001-XM, Repligen) as described previously. 20 Epitope binning and affinity measurement with bio-layer interferometry Classical sandwich epitope binning experiments were performed on an 8-channel Octet RED96 System as described.…”
Section: Generation Of Anti-lilrb1 Mabsmentioning
confidence: 99%
See 2 more Smart Citations